evaluate the commutator [-d^2 / dx^2 , x] f (x)

can anyone please check my work thanks.

[-d^2 / dx^2 , x] f (x) = -2f '(x) -xf "(x) + -xf "(x)

[-d^2 / dx^2 , x] f (x) = -2f '(x) = -2 (d/dx (f(x))

[-d^2 / dx^2 , x] = -2 d/dx

Printable View

- Sep 14th 2008, 03:02 PMmyoplex11commutators
evaluate the commutator [-d^2 / dx^2 , x] f (x)

can anyone please check my work thanks.

[-d^2 / dx^2 , x] f (x) = -2f '(x) -xf "(x) + -xf "(x)

[-d^2 / dx^2 , x] f (x) = -2f '(x) = -2 (d/dx (f(x))

[-d^2 / dx^2 , x] = -2 d/dx - Sep 14th 2008, 04:02 PMtopsquark